(untitled) (Journal of the College of Basic Education, 2022)
In order for human education to be complete, it must include a sound aesthetic appreciation of the great heritage left by man all over the world. The concept of art education is the concept of a comprehensive education for the individual from his birth as a child until he reaches puberty, and throughout his life.The artistic work is based on the integration of its elements with each other and are closely interrelated, and this includes any work of art because it is an intellectual and spiritual product that calls for contemplation and stopping on what it is as art, and not just an ordinary profession or a fleeting gain with the lapse of time.